2013
DOI: 10.1186/2196-1042-14-36
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of condyle position according to sagittal skeletal relationship, assessed by cone beam computed tomography

Abstract: BackgroundThe study aims to compare the condylar position in patients with different anteroposterior sagittal skeletal relationships through a cone beam computed generated tomography (CBCT) imaging generated space analysis.MethodsThis was a retrospective study of clinically justified, previously taken CBCT images of 45 subjects. Based on a proper sample calculation, three groups of 15 CBCT images each were made according to their ANB angle and facial pattern: class I (normo facial pattern) and class II and III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
73
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 19 publications
13
73
4
2
Order By: Relevance
“…Aras and Pasaoglu 19 reported that patients with Class II subdivision malocclusion treated with a Forsus fatigue resistant device were corrected mainly by dentoalveolar changes, without significant skeletal modifications. In that light, the current findings point out a significant cranial base skeletal contribution to the development of Class II subdivision that, although consistent with other reports, 11,20 is beyond the therapeutic range of correction for orthodontists.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Aras and Pasaoglu 19 reported that patients with Class II subdivision malocclusion treated with a Forsus fatigue resistant device were corrected mainly by dentoalveolar changes, without significant skeletal modifications. In that light, the current findings point out a significant cranial base skeletal contribution to the development of Class II subdivision that, although consistent with other reports, 11,20 is beyond the therapeutic range of correction for orthodontists.…”
Section: Discussionsupporting
confidence: 72%
“…2,9,17 In contrast, CBCT images do not present such biases and allow the quantitative and qualitative assessment of bone in actual dimensions. 9,20,21 As such, 3D imaging has opened a new horizon in scientific fields, and new evidence to confirm previous reports or at least show that different ways of thinking are needed. The first case-control investigation that used CBCT technology to assess the etiology of Class II subdivision malocclusion showed different results from what 2D studies had previously provided, 9 and it concluded that the cause of Class II subdivision malocclusion was chiefly a result of a shorter mandible on the Class II side.…”
Section: Discussionsupporting
confidence: 56%
“…CBCT imaging is an accurate way of visualizing the condyle and measuring condyle position and location. 17,18 This retrospective radiographic study is an exploratory study to determine the effects of mandibular positional changes on the upper airway dimensions. .…”
mentioning
confidence: 99%
“…Some of these studies showed a significant relation in changes of condyle position after orthodontic treatment. 16,21,28 For the mean difference in Condylion to TC line before and after orthodontic treatment, Angle class I type 1 is 9.8%, Angle class I type 2 is 11.9%, Angle class I type 3 is 9.3%, Angle class I type 4 is 9.2% and for Angle class I type 5 is 8.2%. The p-value of this five groups of sample were less than 0.05 which showed that that was a statistically significant effect observed in the condylar osition for five types of Angle class I malocclusion before and after orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The position and function of condyle portion of TMJ normally affected by age, facial growth pattern, pathological functional alterations, decreased or increased muscular activity, occlusal force, and dental occlusion changes. 16,17 The objective of orthodontic treatment is to reestablish the normal and balance occlusion characteristics. The maxillary arch should match with the mandibular arch to produce a perfect intercuspation and promote maximum function with minimum effort in consideration of the durability of the stomatognathic system.…”
Section: Discussionmentioning
confidence: 99%